Aptana studio Beginner's Guide. - Deuling, Thomas (Packt Pub., 2013)
Accompanied by the plenty of example code and step-by-step instructions, this book will escalate you from a novice to an expert in no time. This book is for anyone who is looking for an IDE for effectively developing web applications. You will find this book interesting if you are working with common web technologies such as HTML5, JavaScript, or PHP. This book assumes no prior knowledge of Aptana Studio 3 or the named web technologies.